Nghiên cứu hiệu ứng cắt mạch chitosan tan trong nước bằng bức xạ gamma Co-60 - Hiến và cộng sự, Nguyễn Quốc (Vietnam Journal of Chemistry, 2014)
Water soluble chitosan (WSC) with degree of deacetylation (DDA) of about 55% and molecular weight, Mw0 = 25,500 was prepared by reacetylation of chitosan with acetic anhydride. WSC is a new morphology form of chitosan. The effect of radiation degradation of WSC in powder form and in solution 0.5, 1.0, 2.0, 3.0%(w/v) was carried out on a gamma Co-60 source. The molecular weight change by irradiation was measured by GPC method. Results showed that degradation degree was decreased with increasing concentration of WSC. The radiation degradation yields were obtained to be Gd = 4.69 and 402.67 scissions/100eV for WSC in powder and in solution 0.5%, respectively. Results of Gd indicated that WSC was more susceptible to radiation degradation than chitosan (~1 scission/100eV). The polydispersion index Mw0/Mn0 = 1.82 was decreased to 1.63 for WSC (48 kGy) and to 1.57 for WSC solution 0.5% (20 kGy). It indicated that the molecular weight distribution of irradiated WSC was narrower than that of the initial one. X-ray diffraction and IR spectra showed that WSC mainly belonged to amorphous structure and DDA was almost unchanged by irradiation in the dose range studied up to 48 kGy.